2015
DOI: 10.1080/03630242.2015.1061091
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Sensitivity, Perceived Power, and HIV Risk in the Relationships of Low-Income Urban Women

Abstract: The psychological processes associated with HIV infection in long-term relationships differ from those operative in casual sexual encounters, and relatively little research has considered the aspects of personality applicable in the ongoing heterosexual relationships in which women are at greatest risk. Sensitivity to rejection has been linked with efforts to prevent rejection at a cost to the self and therefore may be relevant to the health risks that many women incur in relationships. We examined the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
9
1
1
Order By: Relevance
“…Scores on the overall measure of relationship power (SRPS composite) and subscales with this sample of rural WWIDs were consistent with other studies focused on incarcerated women drug users (Knudsen et al, 2008; Minieri et al, 2014). Most studies examining relationship power have focused on variations in sexual practices (Berenson et al, 2015; Campbell et al, 2009; Knudsen et al, 2008). These studies have shown that a high degree of relationship power is generally associated with healthier and safer decisions in relationships, including whether or not to have sex (Altschular & Rhee, 2015), decisions about birth control (Harvey et al, 2002), and whether to engage in unprotected sexual behaviors (Knudsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on the overall measure of relationship power (SRPS composite) and subscales with this sample of rural WWIDs were consistent with other studies focused on incarcerated women drug users (Knudsen et al, 2008; Minieri et al, 2014). Most studies examining relationship power have focused on variations in sexual practices (Berenson et al, 2015; Campbell et al, 2009; Knudsen et al, 2008). These studies have shown that a high degree of relationship power is generally associated with healthier and safer decisions in relationships, including whether or not to have sex (Altschular & Rhee, 2015), decisions about birth control (Harvey et al, 2002), and whether to engage in unprotected sexual behaviors (Knudsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that women with low perceptions of relationship power are more likely to engage in sexual risk behavior (e.g., Berenson et al, 2015; Campbell et al, 2009). Specifically, among women, higher scores on relationship power subscales including decision-making dominance (Campbell et al, 2009) and relationship control (Knudsen et al, 2008) have been associated with lower sexual risk, including condom use.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity to rejection decreases women's perceived power in a relationship, which in turns increases, the frequency of unprotected sex (Berenson et al, 2015). Previous research suggests that people's willingness and likelihood to negotiate condom use might be affected by rejection sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…In a subsequent study, Romero-Canyas, Reddy, Rodriguez, and Downey (2013) showed that women who were high in RS were more likely to alter valued aspects of themselves in a dating profile to match a prospective dating partner's profile and to react with more hostility when subsequently rejected by the prospective partner. High-RS women in long-term relationships were also more likely to give power over sexual decision-making to partners even when this meant having unprotected sex with a potentially HIV-positive partner (Berenson et al, 2015). London et al (2007) found that women high in sensitivity to gender-based rejection were more likely to self-silence in situations where assertiveness might elicit backlash.…”
Section: The Role Of Acceptance In the Rejection Sensitivity Modelmentioning
confidence: 99%